Local community empowerment and support for future eco-tourism development - Abdullah, Nik Nurasyira; Md Sawari, Siti Salwa (2019)
Ecotourism is one of the niche areas of tourism which is chosen by the tourists to involve especially to the nature lover. This study is to identify the personal benefit, local community empowerment and the relationship between personal benefit and empowerment towards support for future eco-tourism development. Quantitative method were used by using a set of questionnaire. A total of 20 respondents from the local community of Min House Camp, Kelantan have contributed to this survey. The data was analyzed by using IBM Statistical Package for Social Science (SPSS) through several analyses such as descriptive analysis and frequency analysis. The outcomes of this study show the importance of local community empowerment towards eco-tourism development. Hence, the contribution of the study is toward the understanding on how the local community is involved in eco-tourism and to engage local community with the tourism operators.